2023
DOI: 10.1002/chem.202302070
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented Direct Asymmetric Total Syntheses of 5,8’‐Naphthylisoquinoline Alkaloids from their Fully Substituted Precursors Employing a Novel Nickel/N,N‐ligand‐Catalyzed Atroposelective Cross‐Coupling Reaction

Dino Berthold,
Willem A. L. van Otterlo

Abstract: A general and concise synthetic pathway for the preparation of four different 5,8’‐coupled naphthylisoquinoline alkaloids, employing a specially developed nickel/N,N‐ligand‐catalyzed atroposelective Negishi coupling is reported. In the first reported direct atroposelective coupling of the fully substituted precursors, the naturally occurring cross‐coupled products were generally obtained directly in reasonable yields and high optical purities. For the synthesis of the cross‐coupling precursors, we employed a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…Our first indication on the special role of salts present in the Negishi cross-coupling reaction was due to our observations during the optimization of an atroposelective, [9] Ni II /N,N-ligand-catalyzed cross-coupling reactions employing Lassaletta's ligand [10] reaction towards the synthesis of the two naphthylisoquinoline enantiomers Ancistrolikokine J 3 (1) and Ancistrobreveine D (ent-1). [11] To our surprise, the outcome of the synthesis of either of these two enantiomeric natural products was dependent on the method applied for the synthesis of the zinc reagent and its accompanying salt additives, rather than the added salt additives alone. As it is depicted in Table 1, we only obtained the desired natural products 1 or ent-1, respectively, if the zinc reagent was prepared via the transmetallation of an previously generated organolithium or Grignard reagent (Table 1, entry 6 and 7).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our first indication on the special role of salts present in the Negishi cross-coupling reaction was due to our observations during the optimization of an atroposelective, [9] Ni II /N,N-ligand-catalyzed cross-coupling reactions employing Lassaletta's ligand [10] reaction towards the synthesis of the two naphthylisoquinoline enantiomers Ancistrolikokine J 3 (1) and Ancistrobreveine D (ent-1). [11] To our surprise, the outcome of the synthesis of either of these two enantiomeric natural products was dependent on the method applied for the synthesis of the zinc reagent and its accompanying salt additives, rather than the added salt additives alone. As it is depicted in Table 1, we only obtained the desired natural products 1 or ent-1, respectively, if the zinc reagent was prepared via the transmetallation of an previously generated organolithium or Grignard reagent (Table 1, entry 6 and 7).…”
Section: Resultsmentioning
confidence: 99%
“…[15] Noteworthy, its stoichiometric composition corresponded to the transmetallating higher-order ate-species postulated by Böhrer and Organ (Scheme 2b). [5] Applying this procedure for different aryl zinc reagents several other higher-order zincates (11)(12)(13)(14)(15)(16)(17)(18)(19) have been isolated as solids in general high yields (Scheme 2c). [16.17] In our experience, it was reasonably simple to store these higher-order zincate reagents in a glove-box under inert conditions, however, we were also interested in evaluating their stabilities under air, as we handled them usually during reaction set-up.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These compounds have axial chirality and exhibit different biological properties as well as being active against the pancreatic cancer cell line. 105 Recently, Otterlo et al reported 106 the total synthesis of ancistrolikokine J 3 where a C–H borylation followed by methylation is an important step. They borylated ( 154 ) under iridium-catalyzed conditions to achieve ( 155 ), which was then employed for methylation utilizing Hartwig's methylation protocols 107 to obtain ( 156 ).…”
Section: Applicationsmentioning
confidence: 99%